Learning how to conduct medical interviews online for the first time – this is what we learned in Frankfurt am Main - Ullmann-Moskovits, Judith; Farquharson, Maria; Schwär, Miriam; Sennekamp, Monika (GMS Journal for Medical Education, 2021)
Objective: The COVID-19 pandemic made it necessary to convert a course on history taking, in theory and practice, to an online format over a very short time. A key question was whether, and if so to what extent, basic theory and, in particular, the practical skills required to conduct medical interviews can be learned online. Methodology/project description: The teaching program in basic theory was didactically redesigned and asynchronously placed on a learning platform, while the practical program, which consisted of training in conducting history-taking interviews, took place with the help of video conferencing software during synchronous sessions. For the practical sessions, the lecturers received organizational and technical support.Results: Based on initial evaluation results, a positive picture of the conversion has emerged since the course was completed. The need to restructure the course and use new teaching methods because of the COVID-19 pandemic was well accepted by lecturers and students, and the course content was successfully adapted to an online format.Conclusion: Overall, the online format enabled the learning objectives of the course to be successfully achieved. For topics such as non-verbal communication, the evaluation results indicated that a classroom format is preferable. Asynchronous theory teaching was generally very well received. Blended learning formats thus represent an appropriate means of teaching how to conduct medical interviews. Overall, online courses on conducting medical interviews provide students with the opportunity to become acquainted with the use of digital formats to conduct doctor-patient interviews, and to develop the relevant skills.